Analisis Dan Perancangan Koordinasi Sistem Proteksi Rele Arus Lebih Di Pusat Penampungan Produksi Menggung Pertamina Asset Iv Field Cepu - Nugraha, Dio Putra; , Aris Budiman S.T.,M.T (2017)
The short circuit disturbance is an abnormally connection (include an arc) of relatively low impedance, whether made accidentally or intentionally, between two points of fferent potential. Overcurrent relay is one of protection device to isolate the short circuit disturbance. oimprovetheprotection coordination should be planning the coordination of rcurrent relay on Pusat Penampungan Produksi Menggung Pertamina Asset IV Field Cepu. So, to help that plan the writer collecting all electrical data that recuire for analysis, then input the data to the ETAP Power Station 12.6 software to make a single line diagram. After that decide the point where the overcurrent rele are and calculate the value of short circuit at the nearest point where the overcurrent relay are located. From the result of the research shows the value of delay instantaneous in phase 1 is 0.1 second, phase 2 is 0.3 second, phase 3 is 0.5 second, phase 4 is 0.7 second and phase 5 is 0.9 second. This is indicated by simulation curves that don't overlap and the different of delay is 0.2 second which refers to the IEEE 242-1986 standard. In simulation testing report with sources of disturbance in bus 11, 22, and 27 show the circuit breaker can disconnect the current flow step by step from nearest the point of turbance until to the power source.Keywords: ETAP Power Station 12.6, protection coordination, overcurrent relay